2006
DOI: 10.1007/s11948-006-0003-1
|View full text |Cite
|
Sign up to set email alerts
|

Responsible conduct in research

Abstract: Science is not taken for granted any longer. Society, politics and the media pose critical questions tending to censorship or at least control of science. How does science respond? It cannot exist and develop without freedom, but this does not mean freedom to amass knowledge and apply technological applications at any price and without restrictions. Science should be autonomous, but is not value-free. A distinction is made between external and internal social/ethical problems. The former refer to questions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In the rst round of analysis, we inventoried the basic values expressed by these codes, as introduced above. Labels [1] were attached manually by the researchers to extracts of the codes, signifying the value to which reference was made. This involved an interpretive step by the researchers: sometimes a value is explicitly mentioned, but sometimes there is just a description that we interpreted as embodying a certain value.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the rst round of analysis, we inventoried the basic values expressed by these codes, as introduced above. Labels [1] were attached manually by the researchers to extracts of the codes, signifying the value to which reference was made. This involved an interpretive step by the researchers: sometimes a value is explicitly mentioned, but sometimes there is just a description that we interpreted as embodying a certain value.…”
Section: Methodsmentioning
confidence: 99%
“…The rst class of values, relating to truthfulness and more generally to the proper production of scienti c knowledge, often includes values such as methodological rigour, transparency [2], and fair peer review [2][3][4]. Additionally, more abstract values like inquisitiveness [1,5,6] and integrity [7] are frequently mentioned in this respect. The literature draws much inspiration from recent cases of fraud, such as the Stapel case [8] and the Schön case [9].…”
Section: Values In Research Practicesmentioning
confidence: 99%
“…113 Most journals themselves seem unprepared for such troubles; Atlas reviewed the instructions to authors of 122 major biomedical journals and found that only 18% had policies on the retraction of articles. 114 Budd et al present discouraging indications that retracted research continues to be cited, 115 although this practice should eventually disappear as electronic publishing, which allows notices of retraction to be directly linked with retracted articles, 116 However, the same stakeholders in the peer-review system who have been offended by a retraction are owed more than a correction of the scientific record; they are owed an apology. As Souder points out, such apologies are needed so that the culprit will express contrition, the readers will feel reconciled, the other members of the scientific community will be deterred from similar lapses, and the community's faith in the integrity of the system will be restored.…”
Section: Post-publicationmentioning
confidence: 99%
“…We analysed fourteen institutional, national and international codes of conduct -predominantly in the field of biomedicine -to answer these two questions. This paper will continue with brief introductions to the two conceptual pillars guiding our analysis: 1) the basic values that matter to (biomedical) scientific research, as reflected by research codes of conduct; and 2) the idea of attribution of responsibility for realising those values and distributing it between the individual and the institution. The method will be explained then, after which the results will be provided and analysed.…”
mentioning
confidence: 99%